Law enforcement, communication, and community - Giles, Howard (J. Benjamins, 2002)
Given widespread media attention to issues of crime and its prevention, police heroism, and new modes of police-community involvements, this international collection is timely. It is unique in examining ways in which police and citizens communicate across a range of contexts and problem areas. While much attention is afforded the critical roles of communication by police agencies, there has been little recourse to communication science and its theories. Likewise, the latter has not, until recently, concerned itself with analyzing police-citizen interactions. This volume examines the character.